Notes From the Field: Using Grassroots Comics to Break the Silence on Menstruation. (February 2019) - Surbhi,; Anand, Sarita
Attaining safe menstrual health has been a challenge in India due to inadequate sanitation infrastructure, inaccessible or unaffordable hygiene products and lack of awareness. This has been further blindsided by myths and misconceptions on religious and cultural grounds. This article is based on a participatory workshop on menstrual hygiene management held with 23 adolescent girls, who were purposively selected from the village Kadampur, in Tilonia District, Rajasthan, a village close to the sanitary napkin production unit of the Barefoot College. 1 The workshop used the concept of grassroots comics to break the silence on menstruation. Girls shared their own experiences of menstruation through comics and used it as an opportunity to ask questions about this biological process, discuss social taboos and learn about menstrual hygiene. A significant increase in knowledge on various aspects of menstruation and menstrual hygiene was observed.